2008
DOI: 10.1164/rccm.200807-1005oc
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Phenotype of Peripheral Muscle in Chronic Obstructive Pulmonary Disease

Abstract: Comparison of these results with those of studies comparing healthy glycolytic with oxidative muscle suggests that these differences may be attributable to greater type II fiber expression in COPD muscle, as mitochondria within this fiber type have respiratory function similar to that of mitochondria from type I fibers, and yet are intrinsically prone to greater release of H(2)O(2) and more resistant to PTP opening. These results thus argue against the presence of pathological mitochondrial alterations in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
101
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 62 publications
23
101
2
1
Order By: Relevance
“…In electron microscopic examination of lung tissues, we demonstrated that mitochondria in bronchial epithelial cells tended to be fragmented in COPD but not in smokers without COPD, suggesting the fission process dominancy of mitochondrial dynamics in COPD pathogenesis. These results are in accordance with previous reports demonstrating that mitochondria in skeletal muscles from COPD patients tended to be smaller in size accompanied by increased ROS production (16,37,39).…”
Section: Discussionsupporting
confidence: 93%
“…In electron microscopic examination of lung tissues, we demonstrated that mitochondria in bronchial epithelial cells tended to be fragmented in COPD but not in smokers without COPD, suggesting the fission process dominancy of mitochondrial dynamics in COPD pathogenesis. These results are in accordance with previous reports demonstrating that mitochondria in skeletal muscles from COPD patients tended to be smaller in size accompanied by increased ROS production (16,37,39).…”
Section: Discussionsupporting
confidence: 93%
“…Given the tendency for a greater acidosis in patients with COPD (7.06 Ϯ 0.10 in control and 6.95 Ϯ 0.22 in COPD), lower end exercise pH may have slowed the PCr recovery time constant, confounding our interpretation of this parameter. However, despite this difference in pH in this group, the PCr recovery time constant was not significantly different between controls and COPD, which further illustrates that muscle oxidative capacity was preserved in patients with COPD as previously suggested in vivo (20) and in permeabilized muscle fibers (24).…”
Section: Discussionsupporting
confidence: 80%
“…Locomotor muscle oxidative capacity is reduced in COPD (44,45,(175)(176)(177)(178)(179)(185)(186)(187)(188)(189)(190)(191). This has been demonstrated by direct measures of mitochondrial density by electron microscopy (175); by spectrophotometric determination of mitochondrial enzyme activities including citrate synthase (CS), succinate dehydrogenase (SDH), 3-hydroxyacylcoenzyme A dehydrogenase (HAD), and cytochrome oxidase (COX) (176)(177)(178); and by measurements of respiration in permeabilized muscle fibers (179). In line with these observations, the mRNA and/or protein expression of key mitochondrial transcriptional factors and coactivators, including peroxisome proliferator-activated receptor g coactivator-1 (PGC1), peroxisome proliferator-activated receptors (PPAR), and mitochondrial transcription factor A (Tfam), are/is also reduced (180), suggesting a lower drive for mitochondrial biogenesis in COPD muscle.…”
Section: Mitochondrial Function Of Limb Muscle In Copd and Bioenergeticsmentioning
confidence: 99%